Ambiguity, Uncertainty and Implementation - Kristin Taylor; Stephanie Zarb; Nathan Jeschke (International Review of Public Policy)
In policy implementation the roles of ambiguity and uncertainty have been theorized but insufficiently tested. This study contributes to the policy process literature by arguing that ambiguity and uncertainty are two sides of the same coin in implementation. Their effects are linked to the credibility of policy, the clarity of goals, and agency capacity. We analyze ambiguity and uncertainty through the lens of post-disaster policy in local government using primary qualitative data from 22 local government officials across 8 counties and 6 cities that were affected by Hurricane Harvey. We find that the credibility of a policy is evaluated separately from the credibility of the formulator; experience moderates the effects of ambiguity; and uncertainty in implementation has a similar effect as ambiguity and is not lessened with more information. The distinction between the political manipulation of ambiguous circumstances and the rational, technocratic approach to gathering more information to reduce uncertainty may be less clear than previously considered.